How to use ultra-high capacity performance battery cells
By using nanoparticle-sized metal oxides and conductive carbon electrodes in the battery, combined with acidic electrolytes, the erosion and decomposition problems caused by acid groups in the battery are solved, and the battery capacity and cycle life are improved.
Patent Information
- Application Number
- CN201980064709.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-10
- Filing Date
- 2019-09-10
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2039-09-10
AI Technical Summary
The use of acid groups in batteries in prior art will cause erosion of metal current collectors and shells, and the surface of the active catalytic electrode causes electrolyte decomposition, which in turn leads to failure of the battery cell.
Using an electrode containing 20 wt% to 40 wt% nanoparticle size metal oxide and 20 wt% to 40 wt% nanoparticle size conductive carbon, the electrodes may be arranged as an anode or cathode, and an acidic electrolyte or an acidic substance-containing electrolyte is used in the battery.
The battery capacity, circulation capacity and life are improved, specifically manifested as a capacity gain of 100mAh/g or more, and the cycle life is extended to 100 or more charge-discharge cycles.
Smart Images

Figure CN112867932B_ABST
Abstract
Description
[0001] Cross-references to related cases
[0002] This application claims the benefit of U.S. Provisional Patent Application Serial No. 62 / 729,254, filed on September 10, 2018, and is incorporated by reference into this disclosure as if fully set forth herein. Technical Field
[0003] The present disclosure is in the field of materials and methods of construction useful for chemical energy storage and power devices such as, but not limited to, batteries. Background Art
[0004] Metal oxides are compounds of oxygen combined with metals and have the general formula M m O x . They occur in nature but can be artificially synthesized. In synthetic metal oxides, the synthesis method can have a wide range of effects on the surface properties, including its acidity / basicity. Changes in surface characteristics can alter the properties of the oxide, affecting things like its catalytic activity and electron mobility. However, the mechanisms by which surfaces control reactions are not always well characterized or understood. For example, in photocatalysis, surface hydroxyls are thought to promote electron transfer from the conduction band to chemisorbed oxygen molecules.
[0005] Despite the importance of surface properties, the metal oxide literature (scientific papers and patents) has been primarily devoted to generating new nanoscale crystalline forms of metal oxides for improved energy storage and power applications. Metal oxide surface properties have been neglected, and outside of the chemical catalysis literature, very little innovation has involved controlling or modifying the surfaces of known metal oxides to achieve performance targets.
[0006] The chemical catalysis literature is largely devoted to the production of "superacids" - acids greater than pure sulfuric acid (18.4 MH2SO4) - typically for large-scale reactions such as hydrocarbon cracking. Superacidity cannot be measured on the traditional pH scale, but is quantified by the Hammett number. The Hammett number (H0) can be thought of as extending the pH scale to negative numbers less than zero. Pure sulfuric acid has a H0 of -12.
[0007] However, there are many reaction systems and many applications where super acidity is too strong. For example, super acidity can degrade system components or catalyze unwanted side reactions. However, acidity can still be used to provide enhanced reactivity and rate characteristics or improved electron mobility in these same applications.
[0008] The battery literature teaches that acidic groups are detrimental in batteries, where they can corrode metal current collectors and casings and cause degradation of other electrode components. In addition, the prior art teaches that active catalytic electrode surfaces lead to electrolyte decomposition, which can lead to gas generation within the battery cell and ultimately to cell failure.
[0009] There are battery embodiments having synthetic metal oxides that are acidic but not superacidic at least on their surface, and deployed in the anode and / or cathode. In addition, existing battery construction techniques should be updated to take full advantage of the new materials available according to the present disclosure, as well as to take advantage of the gains and improvements that can be achieved using such construction techniques with previously known materials. Summary of the invention
[0010] An embodiment of an ultra-high capacity battery cell has a lithiation capacity of at least 4000 mAhr / g and includes an electrode comprising a layer containing 20 wt% to 40 wt% of a nanoparticle-sized metal oxide and 20 wt% to 40 wt% of a nanoparticle-sized conductive carbon. In a specific embodiment, the metal oxide and the conductive carbon are each 33 wt%. In a further embodiment, the metal oxide and the conductive carbon are each 21 wt%. The electrode can be arranged as an anode or a cathode.
[0011] The battery cell may include at least one other layer that also contains nanoparticle-sized conductive carbon and is arranged adjacent to the layer containing nanoparticle-sized metal oxide. In some embodiments, the other layer is present both above and below the layer containing nanoparticle-sized metal oxide. The nanoparticle-sized metal oxide may be an acidified metal oxide having a pH <5 measured at 5% on its surface at 5wt% water and a Hammett function >-12 (hereinafter, acidified metal oxide, or "AMO"). In other embodiments, the acidified metal oxide may be used in a battery cell or battery construction that is not acidified, substantially not acidified, or not functionalized with an acidic group (hereinafter non-acidified metal oxide or "non-AMO"). AMOs and non-AMOs may be collectively referred to as metal oxides.
[0012] The present disclosure describes materials corresponding to AMOs, non-AMOs, and applications using both. Applications (without limitation) include as catalysts in battery electrode materials, as photovoltaic or photosensitive components, and sensors. Further disclosed are techniques for preparing AMOs and non-AMOs and devices including one of the two. Optionally, the disclosed AMOs are used in combination with acidic substances to enhance their practicality.
[0013] The present application also describes a high capacity electrochemical cell comprising an electrode containing AMO and non-AMO. Techniques for preparing metal oxides and electrochemical cells containing metal oxides are also disclosed. Optionally, the disclosed metal oxides are used in combination with a conductive material to form an electrode. The formed electrode can be used for metallic lithium and conventional lithium ion electrodes as corresponding counter electrodes. Optionally, the disclosed metal oxides are used in combination with an acidic substance to enhance their practicality.
[0014] In some embodiments, the present disclosure provides a layered electrode configuration with low active material (i.e., metal oxide) loading. In some cases, less than 80% active material by weight is used in the electrode. This is in contrast to conventional electrochemical cell technology, which attempts to maximize the loading of active materials and may be greater than or about 80% by weight, such as 90% or 95% or 99%. Although in conventional electrochemical cell technology, high active material loading can be used to increase capacity, the inventors of the present application have found that by reducing the active material loading according to various embodiments of the present disclosure, higher battery capacity is actually allowed. Such an increase in capacity can be achieved at least in part by allowing more absorption of shuttle ions (i.e., lithium ions) because additional physical volume can be obtained when the active material loading level is low. Alternatively or additionally, such an increase in capacity can be achieved at least in part by allowing more active sites to absorb shuttle ions and fewer active sites to be blocked by additional material blocks.
[0015] The metal oxides described include those AMOs in the form of nanomaterials, such as nanoparticles, which can be monodisperse or substantially monodisperse and have a particle size, for example, less than 100 nm. For example, when suspended in water at a specific concentration (e.g., 5 wt%) or resuspended in water after drying, the disclosed AMOs exhibit a low pH, such as less than 7 (e.g., between 0 and 7), and further exhibit a Hammett function H0 greater than -12 (i.e., non-superacidic) at least on the surface of the AMO.
[0016] Optionally, the surface of the AMO can be functionalized, for example with an acidic or other electron withdrawing species. The synthesis and surface functionalization can be accomplished in a "one-pot" hydrothermal process, where the surface of the metal oxide is functionalized as the metal oxide is synthesized from a suitable precursor. In some embodiments, the one-pot process does not require any additional acidification step or steps beyond those required to synthesize the metal oxide itself, and results in the AMO material having the desired surface acidity (but not superacidity).
[0017] Alternatively, surface functionalization occurs using strong electron withdrawing groups ("EWG") such as SO4, PO4 or halogens (Br, Cl, etc.), either alone or in combination with one another. Surface functionalization may also be performed using EWGs that are weaker than SO4, PO4 or halogens. For example, synthesized metal oxides may be surface functionalized with acetate (CH3COO), oxalate (C2O4) and citrate (C6H5O7) groups.
[0018] Although acidic materials are generally considered to be undesirable in batteries because they can corrode metal current collectors and casings and cause degradation of other electrode components, and active catalytic electrode surfaces can lead to electrolyte decomposition, gas generation within the battery cell, and ultimately battery cell failure, the inventors have discovered that acidic materials and components are advantageous in batteries that employ AMO materials in the battery electrodes.
[0019] For example, the combination or use of AMOs with acidic substances can enhance the performance of the resulting materials, systems or devices, thereby producing improved capacity, cycle capacity and life of the device. For example, batteries using AMO materials in combination with acidic electrolytes or electrolytes containing acidic substances as described herein show considerable capacity gains, such as up to 100 mAh / g or more than similar batteries using non-acidified electrolytes or electrolytes lacking acidic substances. In some embodiments, a capacity improvement of 50 mAh / g to 300 mAh / g can be achieved. In addition, an absolute capacity of up to 1000 mAh / g or more can be achieved using batteries with acidified electrolytes or electrolytes including acidic substances. In addition, the cycle life of the battery can be improved by using an acidic electrolyte or an electrolyte containing an acidic substance, such as the cycle life of the battery can be extended by up to 100 or more charge-discharge cycles.
[0020] An exemplary battery cell includes a first electrode, such as a first electrode including a metal oxide (optionally an AMO nanomaterial), a conductive material, and a binder; a second electrode, such as a second electrode including metallic lithium; and an electrolyte located between the first electrode and the second electrode. Optionally, the metal oxide is less than 80% by weight of the first electrode. Example electrolytes include those comprising a metal salt dissolved in a solvent, a solid electrolyte, and a gel electrolyte. Optionally, a separator is positioned between the first electrode and the second electrode.
[0021] Additionally or alternatively, batteries comprising electrodes that are acidic in themselves or electrodes (e.g., cathodes or anodes) comprising acidic substances (e.g., organic acids) may also be beneficial, again contrary to conventional teachings in battery technology. For example, batteries incorporating acidic electrodes or batteries incorporating acidic substances in electrodes may enhance performance and produce improved capacity, cycle capacity, and life, particularly when used in electrodes comprising AMO materials. Capacity gains of up to 100 mAh / g or greater may be achieved. The cycle life of the battery may also be increased by using acidic electrodes or electrodes containing acidic substances, such as battery cycle life may be extended by up to 100 or more cycles. As an example, an acidic electrode or an electrode comprising an acidic substance may exhibit a pH (but not superacidic) of less than 7 when, for example, the components of the electrode are suspended in water at 5 wt % (or resuspended in water after drying).
[0022] An electrode corresponding to the present disclosure may include a layered structure including a first layer set including a conductive material and a second layer set including a metal oxide (e.g., an acidified metal oxide (AMO) nanomaterial). Optionally, the first layer set and the second layer set may be arranged in an alternating configuration. Optionally, the first layer set and the second layer set independently include 1 to 20 layers. Optionally, the first layer set and the second layer set independently have a thickness of 1 μm to 50 μm, 2 μm to 25 μm, 3 μm to 20 μm, 4 μm to 15 μm, or 5 μm to 10 μm. Optionally, the metal oxide accounts for 5 to 90 wt% of the second layer set, such as 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt% or 90 wt%. Optionally, the conductive material and the adhesive each independently constitute 5 to 90wt% of the first layer set, for example 25wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt% or 90wt%.
[0023] Optionally, the first electrode comprises up to 95 wt % of the first electrode's metal oxide, up to 80 wt % of the first electrode's metal oxide, up to 70 wt % of the first electrode's metal oxide, between 1 wt % and 50 wt % of the first electrode's metal oxide, between 1 wt % and 33 wt % of the first electrode's metal oxide, between 15 wt % and 25 wt % of the first electrode's metal oxide, between 55 wt % and 70 wt % of the first electrode's metal oxide, between 5 wt % and 35 wt % of the first electrode's metal oxide. Specific examples of the weight percentage of the metal oxide for the first electrode include 1%, 5%, 11%, 12%, 13%, 14%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 60%, 61%, 62%, 63%, 64%, 65%, etc. Without limitation, the loading (percentage of metal oxide) of the electrode can be in the range of 1-95%, 10-80%, 20-70%, 30-40%, 40-50%, 50-60%, 60-70% or 80-100%. In various embodiments, the loading value can vary by + / -1%, 2%, 5% or 10%. Optionally, the conductive material and the binder each independently constitute a majority of the remainder of the first electrode. For example, the conductive material and the binder each independently constitute 10wt% to 74wt% of the first electrode. Optionally, the conductive material and the binder each together constitute 20wt% to 90wt% of the first electrode. Optionally, the AMO nanomaterial is added as a dopant of 1wt% to 10wt% to a conventional lithium ion electrode, such as graphite, lithium cobalt oxide, etc.
[0024] Various materials can be used for the electrodes described herein. Exemplary metal oxides include, but are not limited to, lithium-containing oxides, aluminum oxide, titanium oxide, manganese oxide, iron oxide, zirconium oxide, indium oxide, tin oxide, antimony oxide, bismuth oxide, or any combination thereof. Optionally, the oxide is in the form of AMO. Optionally, as described herein, the metal oxide comprises one or more electron-withdrawing groups selected from Cl, Br, BO3, SO4, PO4, NO3, CH3COO, C2O4, C2H2O4, C6H8O7, or C6H5O7 and / or is surface functionalized. Exemplary conductive materials include graphite, conductive carbon, carbon black, Ketjen black, or conductive polymers, such as one or more of poly(3,4-ethylenedioxythiophene) (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composites, polyaniline (PANI), or polypyrrole (PPY).
[0025] In some embodiments, an electrode including an AMO nanomaterial is used in combination with other electrodes to form a battery cell. For example, the second electrode of such a battery cell may include graphite, metallic lithium, sodium metal, lithium cobalt oxide, lithium titanate, lithium manganese oxide, lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate, lithium nickel cobalt aluminum oxide (NCA), AMO nanomaterials, or any combination thereof. In a specific embodiment, the first electrode includes SnO2 (in AMO or non-AMO form) and the second electrode includes metallic lithium.
[0026] Various materials can be used for the electrodes described herein. Exemplary metal oxides include, but are not limited to, lithium-containing oxides, aluminum oxide, titanium oxide, manganese oxide, iron oxide, zirconium oxide, indium oxide, tin oxide, antimony oxide, bismuth oxide, or any combination thereof. Optionally, the oxide is in the form of AMO. Optionally, as described herein, the metal oxide comprises one or more electron-withdrawing groups selected from Cl, Br, BO3, SO4, PO4, NO3, CH3COO, C2O4, C2H2O4, C6H8O7, or C6H5O7 and / or is surface functionalized. For example, the conductive material includes graphite, conductive carbon, carbon black, Ketjen black, or a conductive polymer, such as one or more of poly(3,4-ethylenedioxythiophene) (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composites, polyaniline (PANI), or polypyrrole (PPY).
[0027] In various embodiments, a high-capacity battery cell includes a first electrode, the first electrode including a metal oxide nanomaterial, a conductive material, and a binder; a second electrode; and an electrolyte located between the first electrode and the second electrode, wherein the metal oxide nanomaterial accounts for 5-15%, 20-35%, or 55-70% by weight of the first electrode, wherein the metal oxide nanomaterial includes 0-15% by weight of iron oxide and 85-100% by weight of tin oxide. In some embodiments, wherein the metal oxide includes one or more electron-withdrawing groups and / or is surface-functionalized with one or more electron-withdrawing groups, wherein the conductive material includes one or more of graphite, conductive carbon, carbon black, Ketjen black, and a conductive polymer, such as poly 3,4-ethylenedioxythiophene monomer (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composition, polyaniline (PANI), or polypyrrole (PPY), wherein the second electrode includes or consists of metallic lithium.
[0028] Such a high capacity battery cell can exhibit a life cycle of 100 to 1000 charge-discharge cycles without failure, and an open circuit voltage of between 2 V and 4 V when assembled. Optionally, the first electrode comprises a layered structure comprising a first set of layers of conductive material and a second set of layers comprising metal oxide nanomaterials, for example wherein the first set of layers and the second set of layers are provided in an alternating configuration, wherein the first set of layers comprises 1 to 20 layers, and wherein the second set of layers comprises 1 to 20 layers, wherein the first set of layers and the second set of layers each have a thickness between 1 μm and 50 μm, wherein the metal oxide nanomaterials constitute 5-70% by weight of the second set of layers.
[0029] As another example, a battery in which a slurry is used to form the electrode would also be beneficial and contrary to conventional teachings in battery technology. As described herein, optionally, the metal oxide can be formed into a battery electrode by first forming a slurry of the metal oxide with one or more binder compounds, solvents, additives (e.g., conductive additives or acidic additives), and / or other wet processing materials. The slurry can be deposited on a conductive material or a current collector to form an electrode. Optionally, such a slurry and / or solvent can be acidic or include an acidic substance, and again allow the capacity, cycle capacity, and life of the resulting battery to be improved. Optionally, all or part of the solvent can be evaporated, leaving behind the metal oxide material, binder, additives, etc. Optionally, for example, when suspended in water at 5wt% (or dried and then suspended in water), the resulting material (in the case of using AMO) can exhibit its own acidity, for example, having a pH of less than 7 (but not superacidic).
[0030] Various techniques can be used to make the metal oxide. Optionally, preparing the metal oxide includes forming a solution comprising a metal salt, ethanol and water; acidifying the solution by adding an acid to the solution; alkalizing the solution by adding an aqueous base to the solution; collecting a precipitate from the solution; washing the precipitate; and drying the precipitate.
[0031] Optionally, manufacturing the electrode further comprises depositing another conductive layer on the electrode layer, for example, a conductive layer comprising a second conductive material. Optionally, depositing the conductive layer comprises forming a conductive paste using a second conductive material, a second binder, and a second solvent; depositing a conductive paste layer on the electrode layer; and evaporating at least a portion of the second solvent to form the conductive layer. Optionally, manufacturing the electrode comprises forming 1-20 additional conductive layers comprising a conductive material and 1-20 additional electrode layers comprising a metal oxide. For example, the electrode may comprise a layered structure comprising a first set of layers comprising a second conductive material and a second set of layers comprising a metal oxide, for example, wherein the first set of layers and the second set of layers are arranged in an alternating configuration. Exemplary layers include those layers independently having a thickness between 1 μm and 50 μm. Exemplary layers include those layers comprising 10 wt% to 90 wt% of a metal oxide. Exemplary layers include those layers independently comprising 5 wt% to 85 wt% of a conductive material and / or a binder.
[0032] The electrode formed using the method of this aspect may have a metal oxide content of up to 80 wt %.The electrode formed using the method of this aspect may have a conductive material and / or binder content of 10 wt % to 70 wt % of the electrode.
[0033] As described above, optionally, the acidic substance can be included as an additive in any component of the battery, such as an electrode or an electrolyte. Optionally, a battery including a metal oxide according to the present disclosure may include an electrolyte located between the electrodes, wherein the acidic substance is dissolved in a solvent. Such an electrolyte may also be referred to as an acidified electrolyte in this article. Optionally, the electrolyte may include one or more lithium salts dissolved in a solvent, such as LiPF6, LiAsF6, LiClO4, LiBF4, LiCF3SO3, and combinations thereof. It should be understood that the electrolyte may not only be positioned in the space separating the electrodes (i.e., between the electrodes), but may also penetrate or enter the pores of the electrodes, and / or penetrate or enter the pores of any material or structure (e.g., diaphragm) optionally positioned between the electrodes.
[0034] Exemplary acidic materials that can be used in the AMO electrodes and electrolytes described herein include, but are not limited to, organic acids, such as carboxylic acids. Exemplary acidic materials include those that exhibit a pKa of -10 to 7, -5 to 6, 1 to 6, 1.2 to 5.6, or about 4 in water. Specific examples of organic acids include, for example, oxalic acid, carbonic acid, citric acid, maleic acid, methylmalonic acid, formic acid, glutaric acid, succinic acid, methylsuccinic acid, methylenesuccinic acid, citraconic acid, acetic acid, benzoic acid. Exemplary organic acids include dicarboxylic acids, such as those having the general formula Those dicarboxylic acids of the formula: wherein R is a substituted or unsubstituted C1-C20 hydrocarbon, such as a substituted or unsubstituted alkyl, a substituted or unsubstituted alkenyl, a substituted or unsubstituted aromatic or heteroaromatic, a substituted or unsubstituted amine, etc. Exemplary organic acids also include those having the general formula Those organic acids, wherein L is a substituted or unsubstituted C1-C20 divalent hydrocarbon, such as a substituted or unsubstituted alkylene, a substituted or unsubstituted arylene, a substituted or unsubstituted heteroarylene, a substituted or unsubstituted amine, etc. The organic acid may include an organic anhydride, such as having the general formula An organic anhydride, wherein R 1 and R 2 are substituted or unsubstituted C1-C20 hydrocarbons, such as substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted aryl or heteroaryl, substituted or unsubstituted amine, etc. 1 and R 2 A ring can be formed. Exemplary organic anhydrides include any anhydrides of the above-mentioned organic acids. Specific organic anhydrides include, but are not limited to, glutaric anhydride, succinic anhydride, methylsuccinic anhydride, maleic anhydride and itaconic anhydride.
[0035] The effective concentration of the acidic material in one or both of the electrolyte and the AMO electrode includes 0 wt% to 10 wt%, 0.01 wt% to 10 wt%, 0.1 wt% to 10 wt%, 1 wt% to 5 wt%, or 3 wt% to 5 wt%.
[0036] Effective solvents include those used in lithium ion battery systems, such as ethylene carbonate, butylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate and mixtures thereof. Other effective solvents will be appreciated by those skilled in the art. Alternatively, when the acidic substance and the metal salt are dissolved in a solvent to form an electrolyte, the electrolyte itself exhibits acidic conditions (i.e., pH is less than 7).
[0037] Exemplary binders that can be used for the batteries and electrodes described herein include styrene butadiene copolymers (SBR), polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), acrylonitrile, polyacrylic acid (PAA), polyvinyl alcohol (PVA), polyamide imide (PAI), and any combination thereof. Alternatively, a conductive polymer can be used as a binder.
[0038] Other exemplary additives that can be used in the AMOs and electrodes described herein include, but are not limited to, conductive additives. Exemplary conductive additives include graphite, conductive carbon, carbon black, Ketjen black, and conductive polymers, such as poly(3,4-ethylenedioxythiophene (PEDOT), polystyrene sulfonate (PSS), PEDOT:PSS composites, polyaniline (PANI), and polypyrrole (PPY). For example, the conductive additive can be present in the electrode at any suitable concentration, such as at a weight percentage greater than 0 and up to 35 wt%, 40 wt%, or even higher. Optionally, the conductive additive is present at 1 wt% to 95 wt%, 1 wt% to 35 wt%, 1 wt% to 25 wt%, 5 wt% to 40 wt%, 1 0wt% to 40wt%, 15wt% to 40wt%, 20wt% to 40wt%, 25wt% to 40wt%, 30wt% to 40wt%, 35wt% to 40wt%, 40wt% to 45wt%, 40wt% to 50wt%, 40wt% to 55wt%, 40wt% to 60wt%, 40wt% to 65wt%, 40wt% to 70wt%, 40wt% to 75wt%, 40wt% to 80wt%, 40wt% to 85wt%, 40wt% to 90wt%, or 40wt% to 95wt% range is present in the electrode.
[0039] Also described herein are methods of making a battery. An exemplary method of making a battery includes making a metal oxide nanomaterial; forming a first electrode of the nanomaterial or a first electrode including the nanomaterial; forming an electrolyte by dissolving one or more metal salts in a solvent; and positioning the electrolyte between the first electrode and the second electrode. Another exemplary method of making a battery includes making a metal oxide nanomaterial; forming a first electrode of the nanomaterial and one or more metal salts or a first electrode including the nanomaterial and one or more metal salts; and positioning the electrolyte between the first electrode and the second electrode.
[0040] Also disclosed herein is an electrolyte for a battery. For example, the disclosed electrolyte can be used in a battery comprising a first electrode and a second electrode. An exemplary electrolyte comprises a solvent and one or more metal salts dissolved in the solvent. Optionally, an acidic substance, such as an acidic substance different from the one or more metal salts, is dissolved in the solvent.
[0041] As described above, a variety of acidic substances, such as acidic substances including organic acids and / or organic anhydrides, can be used in the disclosed electrolyte. Exemplary organic acids include, but are not limited to, oxalic acid, acetic acid, citric acid, maleic acid, methylmalonic acid, glutaric acid, succinic acid, methylsuccinic acid, methylenesuccinic acid, citraconic acid, or any combination thereof. Exemplary organic anhydrides include, but are not limited to, glutaric anhydride, succinic anhydride, methylsuccinic anhydride, maleic anhydride, itaconic anhydride, or any combination thereof. Examples of other acidic substances are described above. Effective acidic substances include, but are not limited to, those having a pKa of -10 to 7, -5 to 6, 1 to 6, 1.2 to 5.6, or about 4. Optionally, the acidic substance may be present in the electrolyte at any suitable concentration, such as 0.01 wt% to 10 wt%, 0.1 wt% to 10 wt%, 1 wt% to 5 wt%, or 3 wt% to 5 wt%.
[0042] It should be understood that lithium metal salts, such as LiPF6, LiAsF6, LiClO4, LiBF4, LiCF3SO3, can be effective components of the disclosed acidified electrolytes. Exemplary solvents include, but are not limited to, ethylene carbonate, butylene carbonate, propylene carbonate, vinylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate, and mixtures thereof. Exemplary solvents can be used in metal ion batteries, such as lithium ion batteries.
[0043] In addition to the chemistry and battery structures of the present disclosure, new methods of deploying battery cells and batteries constructed according to aspects of the present disclosure are also provided. According to the present disclosure, charging and discharging can be performed at much lower voltages. In addition, battery cells and batteries can be safely discharged to substantially below the nominal voltage of the battery and substantially to zero. Charge and discharge curves and rates can be safely mixed and matched. The load or electronic device utilized by the battery or battery cell of the present disclosure provides the only practical limitation on availability. Similarly, charging can be performed as long as a voltage can actually be obtained from any power source greater than the current discharge voltage. Similarly, charging can be performed as long as a voltage can actually be obtained from any power source greater than the current discharge voltage. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is a simplified cross-sectional view of an exemplary lithium-ion battery cell.
[0045] Figure 2 is another simplified cross-sectional view of a lithium-ion battery cell, with the electrolyte substantially contained by the separator.
[0046] Figure 3 is a schematic diagram of a lithium-ion battery including a plurality of battery cells.
[0047] Figure 4 Shown are the differences in the cyclic voltammograms of AMO tin prepared by the methods disclosed herein relative to commercially available non-AMO tin when cycled against Li.
[0048] Figure 5 It is shown that the total reflectivity of AMO tin oxide is different from the total reflectivity of commercially available non-AMO tin oxide.
[0049] Figure 6 is X-ray photoelectron spectroscopy (XPS) data showing surface functionalization endogenously generated by the synthesis method disclosed herein. The numbers shown are atomic concentration percentages. The rightmost column lists the corresponding pH measured when the synthesized nanoparticles were dispersed in aqueous solution at 5 wt%.
[0050] Figure 7 Electron microscopy images are provided showing the morphological differences between AMO nanoparticles synthesized under the same conditions except using different functionalization groups.
[0051] Figure 8 Shown are the differences in the morphology of AMO nanoparticles synthesized under the same conditions except with two different total reaction times.
[0052] Fig. 9 Representative half-cell data are provided, showing the performance differences between spherical and elongated (needle- or rod-shaped) AMOs when cycled against lithium.
[0053] Fig.10 X-ray photoelectron spectroscopy analysis of the surfaces of AMO nanoparticles synthesized using both strong (phosphorus-containing) and weak (acetic acid) electron withdrawing groups is provided, showing that the atomic concentration of phosphorus is greater than the atomic concentration of bonds associated with acetate groups.
[0054] Fig.11A Data showing visible light active degradation data for different AMOs are provided.
[0055] Fig. 11B Data showing UV light active degradation data for different AMOs are provided.
[0056] Fig.12 is a graph of data comparing two AMOs, one with higher capacity for primary (single use) battery applications and another with higher cycling capability for secondary (rechargeable) battery applications.
[0057] Fig.13 Charge and discharge capacity data as well as coulombic efficiency data are provided, showing that AMOs can lead to enhanced battery performance without degrading battery components or generating gas.
[0058] Fig.14 Capacity and cycling data of AMO in standard, acidified, and alkalized electrolyte systems are shown.
[0059] Fig.15 Capacity and cycling data are shown for an AMO and the same AMO with acidification removed by solvent washing.
[0060] Fig.16 is a graph of temperature and voltage of a battery cell constructed in accordance with the present disclosure and subjected to a needle penetration test.
[0061] Fig.17A is a graph of temperature and voltage of a battery cell constructed in accordance with the present disclosure and subjected to an overcharge test.
[0062] Fig. 17B yes Fig.17A A graph of an overcharge test centered at the beginning of the test.
[0063] Fig.18 is a side view of an example cathode according to aspects of the present disclosure.
[0064] Fig.19 is a bar graph comparing the lithiation capacity of various metal oxides using standard construction techniques compared to construction techniques according to the present disclosure.
[0065] Fig. 20 Several representative discharge curves are provided for various battery chemistries.
[0066] Fig.21 is a representative discharge curve for a battery cell constructed based on AMO tin according to the present disclosure.
[0067] Fig. 22 is a representative discharge curve of a battery cell constructed based on non-AMO materials according to the present disclosure. DETAILED DESCRIPTION
[0068] definition
[0069] For purposes of this disclosure, the following terms have the following meanings:
[0070] Acidic oxide – a term commonly used in scientific literature to refer to binary compounds of oxygen with non-metallic elements. An example is carbon dioxide, CO2. Oxides of some semimetals (e.g. Si, Te, Po) are also weakly acidic in their pure molecular state.
[0071] Acidified Metal Oxide ("AMO") - A term used herein to refer to a binary compound of oxygen and a metallic element that has been synthesized or modified to have an acidity greater than that of its naturally occurring mineral state and also has a Hammet function, H0>-12 (i.e., not superacidic). The average particle size is also smaller than that of the naturally occurring mineral state. The naturally occurring mineral form is not within the scope of the AMO materials of the present invention. However, a synthetic metal oxide that is more acidic than its most abundant naturally occurring mineral form (equivalent stoichiometry) but not superacidic falls within the scope of the present disclosure and can be said to be an AMO material so long as it meets certain other conditions discussed in the present disclosure.
[0072] Acidic - A term commonly used in scientific literature to refer to compounds with a pH less than 7 in aqueous solution.
[0073] Electron Withdrawing Group ("EWG") - A group of atoms or molecules that draws electron density toward itself. The strength of an EWG is based on its known performance in chemical reactions. For example, halogens are known to be strong EWGs. Organic acid groups such as acetate are known to be weak electron withdrawers.
[0074] Hammet function - another method to quantify acidity in highly concentrated acid solutions and superacids, acidity is defined by the following equation: H0 = pK BH+ +log([B] / [BH + ]). On this scale, pure 18.4 molar H2SO4 has a H0 value of -12. The value H0 = -12 for pure sulfuric acid cannot be interpreted as pH = -12, but rather means that the acid species present have an equivalent concentration of an imaginary (ideal) 10 12 mol / L H3O + The protonation capacity of a material is measured by its ability to protonate a weak base. The Hammett acidity function avoids water in its equation. It is used herein to provide a quantitative means of distinguishing AMO materials from superacids. The Hammett function can be correlated with colorimetric indicator tests and programmed temperature desorption results.
[0075] Layered Construction—As used herein, the term "layered construction" shall mean a battery cell composed of discrete deposits of material (which may or may not be the same material) with at least one interface therebetween. The interface may exist during construction but is effectively reduced or eliminated in the final product as specified herein.
[0076] Low loading - active material or mixed layer containing active material, wherein the active material is present in an amount ranging from 10% wgt to 80% wgt.
[0077] Metal oxide – A term commonly used in scientific literature to refer to binary compounds of oxygen and metallic elements. Depending on their position in the periodic table, metal oxides in their pure molecular state range from weakly basic to amphoteric (displaying both acidic and basic properties). Weakly basic metal oxides are oxides of lithium, sodium, magnesium, potassium, calcium, rubidium, strontium, indium, cesium, barium and tellurium. Amphoteric oxides are oxides of beryllium, aluminum, gallium, germanium, astatine, tin, antimony, lead and bismuth.
[0078] Monodisperse - Characterizes particles of uniform size, particles that are substantially separated from one another and do not aggregate into larger particles.
[0079] pH - A functional numerical scale commonly used in scientific literature to specify the acidity or alkalinity of aqueous solutions. It is the concentration of hydronium ions [H3O + As used herein, it describes the relative acidity of nanoparticles suspended in an aqueous solution.
[0080] Surface Functionalization - The attachment of small atomic or molecular groups to the surface of a material.
[0081] Superacid - a substance with an acidity higher than 100% H2SO4 and a Hammett function, H0 < -12.
[0082] Detailed description of the preferred embodiments
[0083] High capacity electrochemical cells and cell components, such as electrodes, for such cells are described herein. The disclosed electrochemical cells and electrodes include metal oxides, which may be AMO or AMO-free nanomaterials, and exhibit high capacity. In an embodiment, the metal oxide is provided in the electrode at a relatively low loading (weight percentage), for example, at a weight percentage of less than 30%, and most of the remainder of the electrode includes a conductive material and a binder. Even at such a low load, a capacity of more than 10,000 mAh / g of AMO nanomaterials was observed. The electrode may be provided in a layered or non-layered configuration. An exemplary layered configuration includes a separate layer comprising an AMO nanomaterial and a low-loaded layer or a layer without AMO. In an embodiment, the AMO-free metal oxide may be layered with a non-AMO metal oxide of other different materials. In an embodiment, in the same layered structure, the layering may include AMO or AMO-free metal oxide. However, the layering of the electrode is completely optional, and high capacity is observed in both layered and non-layered electrodes.
[0084] Reference now Figure 1, a lithium battery cell 100 is shown in a simplified cross-sectional view. The battery cell 100 may include a housing or container 102. In some embodiments, the housing 102 is a polymer or an alloy. The housing 102 chemically and electrically isolates the contents of the battery cell 100 from adjacent battery cells, so that the contents of the battery cell 100 are protected from contamination and from damage to other components of the device in which the battery cell 100 is installed or from damage by other components of the device in which the battery cell 100 is installed. The entire battery may include multiple battery cells arranged in a series and / or parallel configuration, but may optionally include only one battery cell. As is known in the art, the battery may have another housing or fixing mechanism that combines multiple battery cells together.
[0085] The battery cell 100 provides a cathode 104 and an anode 106. When a conductive path is provided between the cathode 104 and the anode 106 outside the battery cell 100, the contents of the battery cell 100 undergo a chemical reaction. As a result of the chemical reaction, electrons are provided at the anode 106, which flow to the cathode 104 via a circuit provided outside the battery (sometimes referred to as a load). At a basic level, during the discharge of the battery cell 100, the material comprising the anode 106 is oxidized, providing electrons that flow through the circuit. The material comprising the cathode 104 (which serves as a receiver of the electrons released by the anode 106) is reduced.
[0086] During discharge, metal cations move from anode 106 to cathode 104 through electrolyte 108 within battery cell 100. In the case of a lithium-based battery, the metal cation may be a lithium cation (Li+). Electrolyte 108 may be a liquid electrolyte, such as a lithium salt in an organic solvent, for example, LiClO4 in ethylene carbonate. Other lithium-based electrolyte / solvent combinations known in the art may be used. In some cases, electrolyte 108 may be a solid electrolyte, such as a lithium salt in polyethylene oxide. Alternatively, the electrolyte may include a polymer electrolyte. Exemplary electrolytes include those described in U.S. Patent Application Publication No. US2017 / 0069931, which is incorporated herein by reference.
[0087] A separator 110 may be used to prevent contact between the electrodes 104, 106. The separator 110 may be a porous material layer that is permeable to lithium ions and electrolyte 108 but is not electrically conductive, thereby preventing internal short circuits in the battery cell 100. As is known in the art, the separator 110 may include glass fibers or may include a polymer that may have a semi-crystalline structure. Other components such as current collectors may also be included in the battery cell 100, but in the embodiment of the present invention, the separator 110 may be a porous material layer that is permeable to lithium ions and electrolyte 108 but is not electrically conductive, thereby preventing internal short circuits in the battery cell 100. As is known in the art, the separator 110 may include glass fibers or may include a polymer that may have a semi-crystalline structure. Figure 1 Not shown in FIG.
[0088] The anode 106, cathode 104, electrolyte 108, and separator 110 together form the complete battery cell 100. Since the separator 110 is porous, the electrolyte 108 can flow into or be contained by the separator 110. Under normal operating conditions, the porosity of the separator 110 allows ions (Li+) to flow between the electrodes 104, 106 via the electrolyte 108. As is known in the art, the separator can be configured to melt and close the internal pore structure to close the battery cell if exposed to excessive heat or a runaway exothermic reaction.
[0089] Most lithium-based battery cells are so-called secondary batteries. They can be discharged and recharged many times before the chemical or structural integrity of the battery falls below acceptable limits. Battery cells and batteries according to the present disclosure are considered primary batteries (e.g., single use) and secondary batteries.
[0090] In the case where battery cell 100 is a secondary battery cell (or part of a secondary battery), it should be understood that battery cell 100 can be recharged individually or as part of an overall system in which multiple battery cells are recharged simultaneously (and possibly in the same parallel or series circuit).
[0091] A reverse voltage is applied to the battery cell 100 to achieve charging. It should be understood that various schemes for effectively recharging lithium batteries can be employed. Constant current, variable current, constant voltage, variable voltage, partial duty cycle, etc. can be employed. Unless stated in the claims, the present disclosure is not intended to be limited to a particular charging method. During charging of the battery cell 100, element 115 represents a voltage source applied between the cathode 104 and the anode 106 to provide electrons from the cathode 105 to the anode 106 and allow a chemical reaction to occur. Lithium ions shuttle from the cathode 104 to the anode 106 through the electrolyte 108 and the separator 110.
[0092] As an example, the cathode 104 or the anode 106 may independently include a metal oxide according to the present disclosure. The metal oxide may be a nanomaterial, may be substantially monodisperse, and may be in AMO or non-AMO form. In order to use an AMO material as a cathode, the anode may correspond to lithium metal or a lithium intercalation material, such as graphite. A non-AMO cathode may also be paired with an anode that may correspond to lithium metal or a lithium intercalation material. Optionally, the electrolyte 108 may include an acidic substance, such as dissolved in an organic solvent with a lithium salt. In addition to or in lieu of using an acidic substance in the electrolyte 108, the electrode (i.e., the cathode 104 or the anode 106) may optionally include an AMO and an acidic substance. Oxalic acid is an exemplary acidic substance.
[0093] Without wishing to be bound by any theory, it is believed that the presence of an acidic substance in the cathode 104 or anode 106 and / or electrolyte 108 improves the surface affinity of the AMO material for lithium ions, resulting in an improved ability to absorb lithium ions during discharge and improved overall capacity compared to a similar battery cell lacking an acidic substance or having an alkalized electrode or electrolyte (i.e., including an alkaline substance). Alternatively or additionally, the presence of an acidic substance may allow for additional active sites in the cathode 104 for absorbing lithium.
[0094] It should be understood that Figure 1 Not drawn to scale. Figure 2 As shown, in most applications, the separator 110 occupies most or all of the space between and in contact with the electrodes 104, 106. In this case, the electrolyte 108 is contained within the separator 110 (but may also intrude into the pores or surface of the anode or cathode). Figure 2 Nor are they necessarily drawn to scale. The actual geometry of the battery cell may range from a relatively thin and flat pouch, to a cylindrical configuration, to a button cell, etc. Battery cell construction techniques such as winding or bobbin or pin-type assemblies may be used.
[0095] The battery cell 100 may also be formed into a commercially viable package by means of current collectors and other components (not shown) known in the art. Although the overall shape or geometry may vary, the battery cell or battery will generally contain electrodes 104, 106 that are separated but not in contact at some location or cross section, and have an electrolyte 108 and possible separator 110 between them. The battery cell may also be configured to have multiple layers of anodes and cathodes. The battery cell may be configured so that two cathodes are located on opposite sides of a single anode, or vice versa.
[0096] A functional battery or working battery for a specific purpose may include multiple battery cells arranged according to the needs of a specific application. Figure 3 An example of such a battery is schematically shown in . Here, the battery 300 includes four lithium battery cells 100 arranged in series to increase the voltage. The capacity can be increased at this voltage by providing an additional battery stack of four battery cells 100 in parallel with the battery stack shown. Different voltages can be achieved by changing the number of battery cells 100 arranged in series.
[0097] A positive electrode 306 is visible on the exterior of the housing 302 of the battery 300. A negative electrode 304 is also provided. The physical form factor of the electrodes 304, 306 may vary depending on the application. Various adhesives, glues, tapes, and / or other securing mechanisms (not shown) may be used within the battery housing 302 to secure the other components. Lithium-based batteries are generally operable, rechargeable, and storable in any orientation (if a secondary battery). As described above, the battery cell 100 may take on a variety of different geometric shapes. Thus, Figure 3 It is not meant to represent any particular physical form factor for battery 300 .
[0098] The battery 300 may also include various auxiliary circuits 308 inserted into the positive electrode 306 and the lithium battery cell 100 within the housing 302 of the battery 300. In other embodiments, the regulating circuit is inserted into the negative electrode 304 and the lithium battery cell 100 instead of or in addition to the insertion of the positive electrode 306 and the lithium battery cell 100. The auxiliary circuit 308 may include short circuit protection, overcharge protection, overtemperature shutdown, and other circuits known in the art to protect the battery 300, the battery cell 100, and / or any load connected to the battery 300.
[0099] The composition of materials selected for cathode 104, anode 106, and electrolyte may be critical to the performance of battery cell 100 and any battery of which battery cell 100 forms a part. In this regard, various examples of AMOs and methods of producing them are provided in the context of the present disclosure. These AMOs are suitable for forming anodes or cathodes in half-cells, battery cells, and batteries. In addition, the AMOs of the present disclosure are compatible with known lithium battery technology including existing anode and cathode components, electrolyte formulations, and separator components. In other embodiments, the same or different preparation, construction, or formation methods used in the case of AMOs, but containing non-AMO materials, may be used.
[0100] It should be understood that the material of the anode 106 selected for a battery cell or battery according to the present disclosure may be less electronegative than the material of the cathode to appropriately complement the cathode 104 material. In a specific embodiment, the disclosed AMO can be used as a cathode for a battery having a lithium metal anode.
[0101] In various embodiments of the present disclosure, cathode 104 comprises an AMO material having an acidic but non-superacidic surface. This is in contrast to previously known materials used as cathodes, such as lithium cobalt or lithium manganese materials. The AMO materials of the present disclosure and methods for making the same are described below. In other embodiments, anode 106 comprises an AMO material of the present disclosure having an acidic but non-superacidic surface.
[0102] The surface of a metal oxide is ideally an array of metal and oxygen centers ordered according to the crystal structure of the oxide. In practice, the array is imperfect and is prone to vacancies, deformation, and surface adhesion effects. In any case, any exposed metal center is a cation (positively charged) and can accept electrons, and therefore acts as a Lewis acid site by definition. The oxygen center is an anion (negatively charged) and acts as a Lewis base site to donate electrons. This results in the amphoteric nature of the metal oxide surface.
[0103] Under normal atmospheric conditions, water vapor present will adsorb onto metal oxide surfaces either molecularly (hydrated) or dissociatively (hydroxylated). Both OH- and H+ species can adsorb onto oxide surfaces. Negatively charged hydroxyl species will attach to metal cation (Lewis acid, electron accepting) centers and H+ will attach to oxygen anion (Lewis base, electron donating) centers. Both types of adsorption result in the presence of the same functional group on the metal oxide surface - the hydroxyl group.
[0104] These surface hydroxyls can be used as proton acids or proton bases because these groups can release or accept protons. The tendency of a single hydroxyl group to become a proton donor or proton acceptor is affected by the coordination of the metal cation or oxygen anion to which it is connected. Defects on the metal oxide surface, such as oxygen vacancies, or the coordination of surface groups with other chemical substances, mean that not all cations and anions are equally coordinated. The number and intensity of acid-base sites will be different. When "totaling" in general on the oxide surface, this can give the surface an overall acidity or alkalinity.
[0105] The number and strength of Lewis acid sites and Lewis base sites (from exposed metal cations and oxygen anions, respectively) and proton acid sites and proton base sites (from surface hydroxyls) add extensive utility and functionality to metal oxides and their use in chemical reactions and device applications. These sites contribute strongly to the chemical reactivity of metal oxides. They can serve as anchoring sites to which other chemical groups or even additional metal oxides can be attached. And they can affect surface charge, hydrophilicity, and biocompatibility.
[0106] One way to modify the surface of metal oxides is to attach small chemical groups or electron withdrawing groups ("EWGs") in a process called surface functionalization. EWGs induce polarization of hydroxyl bonds and promote the dissociation of hydrogen. For example, a stronger EWG should result in a more polarized bond and, therefore, a more acidic proton. The acidity of a Lewis site can be increased by inducing polarization, which promotes the contribution of electrons to that site. When the compound so prepared is placed in water, the acidic protons will dissociate and lower the pH measurement of the aqueous solution.
[0107] Although somewhat imprecise when using solid acid / base systems rather than liquid acid / base systems, conventional pH measurement methods utilizing titration, pH test paper, and pH probes can be used to evaluate the acidity of metal oxides dispersed in aqueous solutions. These measurements can be supplemented by using techniques including, but not limited to, colorimetric indicators, infrared spectroscopy, and programmed temperature desorption data to establish the acidic nature of the metal oxide surface. Surface groups can be examined by standard analytical techniques, including, but not limited to, X-ray photoelectron spectroscopy.
[0108] Surface functionalization can be accomplished post-synthesis, including but not limited to exposing the metal oxide to an acidic solution or vapor containing the desired functional groups. It can also be accomplished by solid phase methods, where the metal oxide is mixed and / or ground with a solid containing the desired functional groups. However, all of these methods require additional surface functionalization steps in addition to the steps required to synthesize the metal oxide itself.
[0109] The synthesis and surface functionalization of the AMO material can be accomplished in a "single-pot" hydrothermal synthesis method or its equivalent, where the surface of the metal oxide is functionalized as the metal oxide is synthesized from a suitable precursor. A precursor salt containing an EWG is dissolved, and the resulting solution is acidified using an acid containing a second EWG. The acidified solution is then alkalized, the alkalized solution is heated, and then washed. A drying step produces a solid AMO material.
[0110] As an example, the following one-pot method was used to synthesize an AMO in the form of a preferred exemplary tin oxide and simultaneously perform surface functionalization:
[0111] 1. First, dissolve 7 grams (7 g) of tin (II) chloride dihydrate (SnCl2 2H2O) in a solution of 35 mL of absolute ethanol and 77 mL of distilled water.
[0112] 2. The resulting solution was stirred for 30 minutes.
[0113] 3. The solution was acidified by dropwise addition of 7 mL 1.2 M HCl and the resulting solution was stirred for 15 minutes.
[0114] 4. The solution was basified by adding 1 M aqueous base dropwise until the pH of the solution was about 8.5.
[0115] 5. The resulting opaque white suspension was then placed in a hot water bath (~60°C to 90°C) while stirring for at least 2 hours.
[0116] 6. The suspension was then washed with distilled water and anhydrous ethanol.
[0117] 7. The washed suspension was dried in air at 100°C for 1 hour and then annealed in air at 200°C for 4 hours.
[0118] This method yields a tin AMO surface-functionalized with chlorine, which, when resuspended and measured at 5 wt% in aqueous solution at room temperature, has a pH of about 2. By definition, its Hammett function H0> -12. Although an open system such as a flask is described herein, a closed system such as an autoclave may also be used.
[0119] Using the one-pot process disclosed above, a number of AMOs have been synthesized. Table 1 below describes the precursors and acids that have been used. In some cases, dopants were also used.
[0120]
[0121]
[0122] Wherein Ac is an acetate group having the chemical formula C2H3O2.
[0123] In some embodiments, the carbon chain length of the electron withdrawing group is 6 or less and / or the organic mass is 200 or less (AMU). In some embodiments, the carbon chain length of the electron withdrawing group is 8 or less, or 10 or less, and / or the organic mass is 500 or less.
[0124] It should be understood that the parameters of the method can change. These parameters include but are not limited to the type and concentration of reagent, the type and concentration of acid and alkali, reaction time, temperature and pressure, stirring speed and time, the quantity and type of washing steps, the time and temperature of drying and roasting and the gas exposure during drying and roasting. Experimental design method can be used to change individually or in any combination. In addition, other metal oxide synthesis methods--such as spray pyrolysis method, vapor phase growth method, electrodeposition method, solid phase method and hydrothermal or solvent thermal treatment method--can be used to achieve the same or similar result as method disclosed herein.
[0125] Various annealing conditions can be used to prepare AMO nanomaterials. Exemplary annealing temperatures can be lower than 300°C, for example, from 100°C to 300°C. Exemplary annealing times can range from about 1 hour to about 8 hours or longer. Annealing can be performed under various atmospheric conditions. For example, annealing can be performed in air at atmospheric pressure. Annealing can be performed under elevated pressure (greater than atmospheric pressure) or reduced pressure (less than atmospheric pressure or in a vacuum). Alternatively, annealing is performed in a controlled atmosphere, for example, under an inert gas (e.g., nitrogen, helium or argon) or in the presence of an oxidizing gas (e.g., oxygen or water).
[0126] Various drying conditions can be used to prepare AMO nanomaterials. Exemplary drying temperatures can be from 50°C to 150°C. Exemplary drying times can range from about 0.5 hours to about 8 hours or longer. Drying can be carried out under various atmospheric conditions. For example, drying can be carried out in air at atmospheric pressure. Drying can be carried out under elevated pressure (greater than atmospheric pressure) or reduced pressure (less than atmospheric pressure or in a vacuum). Alternatively, drying is carried out in a controlled atmosphere, for example, under an inert gas (e.g., nitrogen, helium or argon) or in the presence of an oxidizing gas (e.g., oxygen or water).
[0127] The performance characteristics of the AMO nanomaterials disclosed herein are different from those of non-acidified metal oxide nanoparticles. As an example, Figure 4 The differences in the cyclic voltammograms of AMO tin prepared by the single-pot process relative to commercially available non-AMO tin when cycled relative to lithium are shown. For example, the surface functionalized AMO materials exhibit better reversibility than the non-AMO materials. The presence of different peaks in the CV of the AMO materials may indicate that multiple electron transfer steps occur during charge / discharge. For example, the peaks at higher voltages may indicate direct oxidation / reduction of the AMO material, while the peaks at lower voltages may be due to changes in the material structure of the AMO material (i.e., alloying).
[0128] As another example, Figure 5 The total reflectivity of the AMO tin oxide is shown to be different from the total reflectivity of the commercially available non-AMO tin oxide. The data shows that AMO has a lower band gap and therefore has more desirable properties as a component of a photovoltaic system in addition to being used as an anode or cathode according to the present disclosure.
[0129] AMO materials may be considered to have a general formula
[0130] M m O x / G
[0131] in
[0132] M m O x is a metal oxide, m is at least 1 and not more than 5, and x is at least 1 and not more than 21;
[0133] G is at least one EWG that is not hydroxide; and
[0134] / Just distinguishing between metal oxides and EWG means there is no fixed mathematical relationship or ratio between the two.
[0135] G may represent a single type of EWG or more than one type of EWG.
[0136] An exemplary AMO is acidified tin oxide (Sn x O y ), acidified titanium oxide (Ti a O b ), acidified iron oxide (Fe c O d ) and acidified zirconium oxide (Zr e O f ). Exemplary electron withdrawing groups ("EWG") are Cl, Br, BO3, SO4, PO4, and CH3COO. Regardless of the specific metal or EWG, according to the present disclosure, the AMO material is acidic but not superacidic, produces a pH <7 when suspended in aqueous solution at 5 wt%, and produces a Hammett function, H0>-12, at least on its surface.
[0137] The AMO material structure can be crystalline or amorphous (or a combination thereof), and can be used alone, or in combination with each other, or in combination with non-acidified metal oxides, or in combination with other additives, adhesives, or conductive aids known in the art as a composite material. In other words, the electrode prepared using the AMO of the present disclosure may or may not include other materials. In one embodiment, the AMO can be stacked on a conductive material to form a cathode 104. In some embodiments, the AMO material is added to a conductive auxiliary material such as graphite, carbon black, or conductive carbon (or its equivalent) at 10wt% to 80wt% and 90wt% to 95wt% or more. In a preferred embodiment, AMO is added at 10wt%, 33wt%, and 80wt%.
[0138] In order to maximize the amount of total surface area available, the AMO should be in nanoparticle form (i.e., less than 1 micron in size) and substantially monodisperse. More preferably, the nanoparticle size is less than 100 nm, and more preferably, less than 20 nm or 10 nm. In some embodiments, using non-AMO metal oxides, the material can still be in nanoparticle form and can be substantially monodisperse. Likewise, the size of the nanoparticles can be less than 100 nm, and preferably less than 20 nm or less than 10 nm.
[0139] Mixed metal AMOs (in which another metal or metal oxide is present in addition to the pure oxide or binary oxide) have been reduced to practice to form anodes for use in half cells, cells, and batteries. These mixed metal AMOs can be considered to have the general formula
[0140] M m N n O x / G and M m N n R r O x / G
[0141] in:
[0142] M is a metal and m is at least 1 and not more than 5:
[0143] N is a metal and n is greater than 0 and not greater than 5;
[0144] R is a metal and r is greater than 0 and not greater than 5;
[0145] O is the total oxygen associated with all metals, x is at least 1 and not more than 21;
[0146] / only distinguishes between metal oxides and electron-withdrawing surface groups, indicating that there is no fixed mathematical relationship or ratio between the two; and
[0147] G is at least one EWG that is not hydroxide.
[0148] G may represent a single type of EWG or more than one type of EWG.
[0149] Some prior art mixed metal oxide systems (of which zeolites are the most notable examples) exhibit strong acidity, even though each pure oxide does not exhibit strong acidity. Preferred embodiments of the mixed metal AMOs disclosed herein differ from those systems in that any embodiment must include at least one pure M that is acidic (but not superacidic). m O x / G form of AMO. The preferred mixed metal and metal oxide system is Sn x Fe c O y+d and Sn x Ti a O y+b , where y+d and y+b can be integer or non-integer values.
[0150] In another embodiment, the mixed-metal AMO material is produced by a one-pot process with one modification: the synthesis starts with two metal precursor salts in any ratio instead of one metal precursor salt. For example, step 1 of the one-pot process can be modified as follows: First, 3.8 g of tin(II) chloride dihydrate (SnCl 22 H2O) and 0.2 g lithium chloride (LiCl) were dissolved in a solution of 20 mL anhydrous ethanol and 44 mL distilled water.
[0151] The three metal precursor salts shown in Table 1 may also be used in any proportion. Depending on the desired product, the metal precursor salts may have the same or different anionic groups; may be introduced at different points in the synthesis; may be introduced as a solid or introduced into a solvent. In some embodiments, the first metal precursor salt may be used for the primary structure (i.e., a larger proportion) of the resulting AMO, and the second (and optionally the third) metal precursor salt may be added as a dopant for the resulting AMO or as a minor component.
[0152] The one-pot experiments led to seven notable findings. First, in all cases, surface functionalization and acidity were generated endogenously (see Figure 6 ), rather than being generated after the synthesis. Unlike the surface functionalization methods of the prior art, the one-pot method does not require any additional surface functionalization step or steps beyond those required for the synthesis of the metal oxide itself, and does not use hydroxyl-containing organic compounds or hydrogen peroxide.
[0153] Second, the method can be widely promoted on a wide range of metal oxides and EWGs. Using the method disclosed in the present invention, metal oxides of iron, tin, antimony, bismuth, titanium, zirconium, manganese and indium were synthesized, and surface functionalization was performed with chloride, sulfuric acid, acetic acid, nitric acid, phosphoric acid, citric acid, oxalic acid, boric acid and bromide at the same time. Mixed metal AMOs of tin and iron, tin and manganese, tin and manganese and iron, tin and titanium, indium and tin, antimony and tin, aluminum and tin, lithium and iron, and lithium and tin were also synthesized. In addition, EWGs that are weaker than halogens and SO4 but still produce acidic but non-superacidic surfaces can be used to achieve surface functionalization. For example, the method is also used to synthesize AMOs functionalized on the surface with acetate (CH3COO), oxalate (C2O4) and citrate (C6H5O7). Various examples are described below.
[0154] Third, there is a synergistic relationship between EWG and other properties of nanoparticles such as size, morphology (e.g., plate-like, spherical, needle-like, or rod-like), oxidation state, and crystallinity (amorphous, crystalline, or a mixture thereof). For example, morphological differences occur between AMO nanoparticles synthesized under the same conditions except that different EWGs are used for surface functionalization (see Figure 7 ). Surface functionalization can act to "pin" the size of the nanoparticles, stopping their growth. This pinning can occur in only one dimension of the nanoparticle, or it can occur in more than one dimension.
[0155] Fourth, the properties of AMOs are very sensitive to the synthesis conditions and processes. For example, differences in the morphology and properties of AMO nanoparticles occur when they are synthesized under the same conditions except with two different total reaction times (see Figure 8 and Fig. 9). Experimental design methods can be used to determine the best or optimal synthetic conditions and processes to produce a desired property or set of properties.
[0156] Fifth, both the anions present in the precursor salt and the anions present in the acid contribute to the surface functionalization of the AMO. In a preferred embodiment, a tin chloride precursor and hydrochloric acid are used for the synthesis of tin AMOs. The performance of these particles is different from the embodiments in which a tin chloride precursor and sulfuric acid are used, or from the embodiments in which a tin sulfate precursor and hydrochloric acid are used. Therefore, for some embodiments, matching the precursor anions and the acid anions is preferred.
[0157] Sixth, when using a precursor with a weak EWG and an acid with a strong EWG, or vice versa, the strongly withdrawing anions will dominate the surface functionalization. This opens up a wider range of synthetic possibilities, allowing functionalization with ions that are not readily available in both the precursor salt and the acid. It can also allow mixed functionalization with strong and weak EWGs. In one example, a tin acetate precursor and phosphoric acid were used to synthesize a tin AMO. X-ray photoelectron spectroscopy analysis of the surface showed that the atomic concentration of phosphorus was greater than the atomic concentration of bonds associated with acetate groups (see Fig.10 ).
[0158] Seventh, and finally, while the disclosed method is a general process for synthesizing AMOs, the synthesis process and conditions can be adjusted to produce sizes, morphologies, oxidation states, and crystalline states deemed desirable for different applications. As an example, catalytic applications may require AMO materials that are more active in visible light (see Fig.11A ) or AMO materials that are more active in UV light (see Fig. 11B ).
[0159] In another example, AMO materials can be used as battery electrodes. A primary (single use) battery application may require an AMO with properties that result in the highest capacity, while a secondary (rechargeable) battery application may require the same AMO but with properties that result in the highest cycling capability. Fig.12 Comparison of the cycling capabilities of two different batteries composed of AMO materials including chlorine-containing AMO and sulfur-containing AMO. The AMO materials improve battery performance without degrading battery components or generating gas (see Fig.13 ). This is exactly the opposite of what the prior art teaches.
[0160] exist Fig.13In the , the charge and discharge cycling capability of the battery constructed as a half-cell of AMO nanomaterial electrodes relative to lithium metal is shown, which shows a cycling capability of up to 900 charge and discharge cycles while still maintaining effective capacity and excellent coulombic efficiency. Such long cycling capability is very excellent, especially relative to the lithium metal reference electrode, because lithium metal is known to grow dendrites even during low cycle numbers, which can expand and lead to dangerous and fatal failure of the battery cell.
[0161] According to the present disclosure, in a complete battery cell, an anode 106 including the disclosed AMO can be used with a known electrolyte 108 and a battery including, for example, lithium cobalt oxide (LiC o O2) can be used with a cathode 104 of a known material. Similarly, the material constituting the separator 110 can be extracted from materials currently known in the art. In another embodiment, the anode 106 can include a disclosed non-AMO metal oxide with a known electrolyte 108 and a cathode 104 comprising a known material, and / or constructed according to a known method.
[0162] In a complete battery cell, a cathode 104 comprising the disclosed AMO can be used with a known electrolyte 108 and an anode 106 comprising a known material that exhibits a lower electronegativity than the disclosed AMO, such as carbon on copper foil. The materials comprising the separator 110 and the electrolyte 108 can also be derived from those currently known in the art as discussed above. In another embodiment, the cathode 104 can include a disclosed non-AMO metal oxide with a known electrolyte 108 and a cathode 104 comprising known materials, and / or be constructed according to known methods.
[0163] Various layering and other enhancement techniques may be employed to maximize the capacity for maintaining lithium ions to power the battery cell 100. It should also be understood that the battery cell 100 may be used as a secondary (e.g., rechargeable) battery according to the present disclosure, but may also be used as a primary battery. Although the anodes and cathodes of the present disclosure are suitable for reversible battery chemistry, the battery cell or battery constructed as described herein may be satisfactorily used as a primary battery cell or battery.
[0164] In the battery industry, the term "formation" is used to refer to the initial charging or discharging of a battery at a production facility before the battery is ready for use. The formation process can often be quite slow, and multiple charge-discharge cycles may be required to transform the manufactured active materials into a form more suitable for battery cell cycling. These transformations can be changes in the structure, morphology, crystallinity, and / or stoichiometry of the active materials.
[0165] In some embodiments, cells and batteries constructed in accordance with the present disclosure do not require initialization and are therefore ready for use as primary cells and batteries when assembled. In other cases, limited or rapid formation may be employed. In addition, by using the cells and batteries of the present disclosure as primary batteries that are not intended to be recharged, some safety issues that may be inherent to lithium battery chemistry are mitigated, as it is known in the art that safety issues occur more frequently during battery cycling. However, after an initial single discharge, the cells and batteries disclosed herein are suitable for use as secondary battery systems that may undergo many charge-discharge cycles, such as up to tens, hundreds, or even thousands of cycles.
[0166] In some embodiments according to the present disclosure, cathode 104 includes tin oxide (SnO2) nanoparticles in a non-AMO form. The tin oxide nanoparticles can be substantially monodisperse. According to embodiments of the present disclosure, titanium dioxide (TiO2), iron oxide (FeO, Fe2O3, Fe3O4) or another metal oxide can replace tin oxide. Known electrolytes 108, anodes 106, and separators 110 or those otherwise described in the present disclosure can be used in these embodiments.
[0167] It should be understood that other battery configurations using the AMO and non-AMO metal oxides disclosed herein are possible. For example, the battery may include a first electrode comprising a metal oxide disclosed herein (possibly in the form of monodispersed nanoparticles), a second electrode, and an electrolyte located between the first electrode and the second electrode. As an example, in a lithium-ion battery, the first electrode can be used as a cathode or an anode. For example, when operating as a cathode, the second electrode may correspond to lithium metal, graphite, or another anode material. As another example, when operating as an anode, the second electrode may correspond to LiCoO2, LiMn2O4, LiNiO2, or another cathode material. Materials that can be used for the second electrode include, but are not limited to, graphite, lithium metal, sodium metal, lithium cobalt oxide, lithium titanate, lithium manganese oxide, lithium nickel manganese cobalt oxide (NMC), lithium iron phosphate, lithium nickel cobalt aluminum oxide (NCA), or any combination thereof.
[0168] It should be understood that the AMO materials disclosed herein can also be added as dopants to conventional lithium-ion battery cell anodes and / or cathodes, for example, in an amount of 0.01 wt% to 10 wt%, or added to electrodes, for example, in an amount of about 1 wt%, 5 wt% or 10 wt%. The disclosed AMO materials provide a great capacity for storing lithium atoms, and by adding these materials to conventional lithium-ion battery cell electrodes. As a specific example, the electrode includes LiCoO2 and AMO. As another example, the electrode includes a carbon material (e.g., graphite) and AMO.
[0169] The metal oxides disclosed herein may optionally be used with acidic components such as adhesives, acidic electrolytes or acidic electrolyte additives. This may be in the case of anodes, cathodes, half-cells, complete cells, integrated batteries or other components. The inventors were surprised to find that, compared to batteries that do not include acidic substances, including acidic components and / or acidic substances (e.g., organic acids or organic anhydrides) in batteries comprising AMO materials results in increased capacity. Similarly, the prior art teaches not to use acidic substances because these substances may degrade metal current collectors and housings and cause other electrode components to deteriorate.
[0170] like Fig.14 As shown, it provides comparative cycling capacity data for multiple AMO-based batteries, which are formed from the same materials and structure, except that one has a standard electrolyte, one has an alkalized electrolyte, and one has an acidified electrolyte. The batteries include the following construction: all cathodes include the same AMO material; all anodes are lithium metal; the standard electrolyte is a 1:1:1 mixture of dimethylene carbonate, diethylene carbonate, and ethylene carbonate and 1M LiPF6; the acidified electrolyte is a 3wt% succinic anhydride standard electrolyte; the alkalized electrolyte is a 3wt% dimethylacetamide standard electrolyte. All batteries are cycled at the same discharge rate. As shown, the battery with the acidified electrolyte system exhibits the best cycling capacity, maintaining the highest capacity at the maximum number of cycles.
[0171] Fig.15 Comparative cycling capacity data for two different additional cells having the same cell configuration (including an acidified electrolyte) are provided, except that the AMO material of one cell was deacidified by washing with a solvent. The cells included the following configuration: the cathode included the AMO material; the electrolyte was a 1:1:1 mixture of dimethylene carbonate, diethylene carbonate, and ethylene carbonate with 1M LiPF6 and 3wt% succinic anhydride; and the anode was lithium metal. The cells were cycled at the same discharge rate. The cell with the acidified AMO material exhibited a higher capacity retention capability relative to the number of cycles, indicating that the acidified surface of the AMO can interact with the acidified electrolyte to provide enhanced performance.
[0172] Currently, lithium batteries are considered a safety risk in certain situations. For example, airline regulations currently require that lithium batteries be partially discharged in order to be carried in the cargo hold. Fires have been reported in devices using lithium batteries caused by runaway exothermic reactions. In addition, lithium fires are difficult to extinguish using commonly deployed fire suppression systems and equipment. For these reasons, lithium-containing compounds are used rather than metallic lithium in many commercial battery cells.
[0173] However, the use of lithium-containing compounds rather than lithium metal in the anode limits the amount of lithium available for reaction and incorporation into the cathode during discharge, and therefore also limits the capacity of such batteries. However, the currently disclosed AMO materials not only show a large absorption of lithium during discharge, but also show enhanced safety characteristics. For example, when a battery cell including a cathode containing an AMO material and a lithium metal electrode is subjected to safety tests, such as a pinprick test, a short circuit test, and an overcurrent test, the battery cell performs well and does not appear to pose an unacceptable risk of fire or explosion. This may be because the AMO passivates the lithium metal in the battery cell or battery. Even if solid or pure lithium is used as the anode, the device using the AMO disclosed herein as the cathode does not appear to pose an unacceptable risk of fire or explosion. The novel safety results may also be attributed to the low operating voltage of the battery cell disclosed herein, which in some embodiments is <1.5V compared to the conventional lithium ion operating voltage of >3.0V.
[0174] Several cells were constructed with cathodes containing AMO (SnO2) according to the disclosure herein. The cathode was prepared from a composition of AMO (SnO2), Ketjen Black (KB), polyvinylidene fluoride (PVDF) and polyaramid (PAA) in a ratio of 63 / 10 / 26.1 / 0.9 (by volume). ... 2 A double-sided layer of this composite was prepared. Six such layers constituted the cathode. The area of the prepared cathode was 9 cm x 4 cm. A separator was obtained from Targrey Technology International Inc., having a 25 μm thick polypropylene layer. The area of the separator was 9.4 cm x 4.4 cm 2 The electrolyte was prepared with 1M LiPF6 in a solvent of ethylene carbonate, diethyl carbonate and dimethyl carbonate (volume ratio of 1 / 1 / 1). The anode was a 50 μm thick lithium metal layer with an area size of 9.2 cm × 4.2 cm 2 .
[0175] Two of the constructed cells were discharged prior to safety testing and were found to have an actual capacity of 1.7 Ah and a specific capacity of 1575 mAh / g SnO2.
[0176] Fig.16 is a graph of data for the temperature and voltage of a battery cell constructed as described above and subjected to a needle penetration test. The test was conducted at room temperature and no incidents (such as fire) were observed. It can also be seen that the temperature and voltage remained stable.
[0177] Fig.17Ais a graph of data of temperature and voltage of a battery cell constructed as described above and subjected to an overcharge test. A current of 1 A was applied. Other than some gassing from the battery cell, no adverse events were observed within the time frame of the test. Fig. 17B yes Fig.17A A graph of overcharge test results centered at the beginning of the test.
[0178] It should be understood that the examples constructed for the purpose of penetration testing are not intended to limit the entire disclosure herein. Cells and batteries of various sizes, capacities, and materials may be constructed in accordance with the disclosure herein. Utilizing the AMO disclosed herein, such batteries will gain the benefits of increased safety demonstrated herein, whether such safety is ultimately due to lithium passivation, lower voltage, or other factors.
[0179] Embodiments of electrochemical cells incorporating AMO material as a cathode and lithium as an electrode construction have been tested and successfully undergo up to 900 or more charge-discharge cycles without catastrophic and destructive failure. In other words, embodiments of electrochemical cells incorporating AMO material as a cathode and lithium as an electrode construction have been tested and successfully undergo up to 900 or more charge-discharge cycles and still maintain a charge and retain a useful capacity.
[0180] Without wishing to be bound by any theory, the enhanced safety provided by the use of AMO-based cathode materials in lithium battery cells may result from the ability of the AMO materials to passivate lithium metal and prevent dendrite formation. The inventors have observed that upon cycling, the lithium metal anode does not appear to grow or otherwise form dendrites, but the lithium anode exhibits a softer and less crystalline appearance structure. In some embodiments, the metallic lithium anode may be passivated, for example, by cycling as a component of an electrochemical cell described herein, and then removed from the electrochemical cell and used as an electrode in a new electrochemical cell having a different cathode. In addition, battery cells constructed in accordance with the present disclosure utilize low operating voltages, such as 1 to 2 volts, in contrast to the typical voltages of lithium or lithium ion battery cells, which typically operate at around 3-4.2 volts. This difference in operating voltage may explain in part the safety of the disclosed battery cells.
[0181] With respect to the construction of a battery cell or battery using lithium as an anode according to the present disclosure, in some embodiments, the entire anode (100%) is metallic lithium. The metallic lithium may only be substantially pure, in that a small percentage of the anode may contain trace elements and impurities that do not affect the performance of the battery cell or battery in a measurable manner. In various embodiments, the anode contains at least 50%, 55%, 60%, 65%, 75%, 80%, 85%, 90%, or 95% metallic lithium.
[0182] For the purposes of this disclosure, the term "metallic lithium" refers to lithium in a neutral atomic state (i.e., a non-ionic state). The term metallic lithium is intended to be distinguished from other forms of lithium including lithium ions and lithium compounds. The term metallic lithium may refer to neutral atomic lithium present in a mixture containing lithium atoms (e.g., a mixture of lithium with other elements, compounds, or substances). The term metallic lithium may refer to neutral atomic lithium present in a lithium alloy (e.g., a metal mixture including lithium and one or more other metals). The term metallic lithium may refer to neutral atomic lithium present in a composite structure including lithium and one or more other materials. An electrode including or containing metallic lithium may include materials other than lithium, but it should be understood that metallic lithium may correspond to the active material of such an electrode. In some cases, the anode in an electrochemical cell includes metallic lithium.
[0183] For the purposes of this disclosure, metallic lithium may be considered to refer to lithium that does not react with any other element to form a compound (at least in a cell or battery configuration). In some embodiments, a portion of the anode may be metallic lithium, while a portion of the anode may be a lithium compound containing various percentages of lithium that reacts with other elements to form a lithium compound. The metallic lithium may be arranged to be geometrically isolated on or within the anode relative to the lithium compound portion of the anode.
[0184] Reference now Fig.18 , which provides a perspective view of a cathode 1800 according to aspects of the present disclosure. Fig.18 Not drawn to scale. Cathode 1800 contained 33.3% SnO2 in the form of AMO. AMO was prepared according to the method described above. To form carbon layer 1804, Ketjen Black EC-300J (specific surface area (SA): ∼800 m 2 / g) slurry was prepared and coated on a copper foil 1802 having a thickness of 10 μm. The slurry composition was 80% Ketjen black and 20% PVDF by weight. The coated tape was dried in a vacuum oven at 100°C.
[0185] To form the carbon / SnO2 electrode layer 1806, AMO SnO2, Ketjen black and PVDF (33.3% each by weight) were mixed together and a slurry was prepared by adding NMP solvent and the slurry was coated on a portion of the Ketjen black coated copper foil (1802, 1804). The resulting coated tape was dried in a vacuum oven at 100°C (overnight) and rolled at room temperature. The thickness of the coated tape was measured using a micrometer in the SnO2 coated area and the Ketjen black coated area only. The thickness of the Ketjen black layer 1804 was about 8 μm; the thickness of the electrode layer 1806 was about 2 μm. The thickness of the foil layer was about 10 μm giving a cathode 1800 with a total thickness of about 18 μm.
[0186] The calendered tape was punched into discs in the coated areas of Ketjen Black (only) and SnO2. The weight of the Ketjen Black disc was subtracted from the weight of the SnO2 coated disc to obtain the total mass of the electrode layer. In the case of one test cell type, the total mass of the electrode material was 0.0005 g (after subtracting the weight of the Ketjen Black coated disc), and the active material content was 0.000167 g (33.3% of the total mass).
[0187] Some important elements of cathode 1800 are (1) lamination, use of carbon undercoat (2) use of Ketjen black high surface area electrocarbon in both undercoat and topcoat (3) 33% active material topcoat, and (4) thin (about 2 μm) topcoat. All of these parameters may be further developed.
[0188] In some embodiments, carbons other than Ketjen Black may be used. Binders other than PVDF may be used. The cathode may be constructed in one or more layers. The percentage of active material may be greater than or less than 33%. The thickness of one or more layers may be greater than or less than 2 μm. Various current collectors may be used in order to optimize the battery cell configuration.
[0189] It should be understood that the above examples provide a situation where the loading of active material in an electrode is lower than what has been thought to promote optimal performance and capacity. As previously mentioned, the traditional preference for active loading is 90%, 95% or higher (if possible). According to this embodiment, the active loading can be less than 80% w / w. In some embodiments, the calculation of the active loading percentage can be the total active loading of the various conductive layers including the electrode. For example, when combined with a conductive layer containing little or no active material, a layer with a higher (but still low according to the teachings of the prior art) active material loading of 33% can provide a total active loading of 23% on the electrode. In various embodiments, the total active material loading of the electrode is less than 63% at most. In another embodiment, the total loading of active material is 23% to 33%. In yet another embodiment, the total loading of active material is 11% to 14%.
[0190] Materials according to the present disclosure (e.g., AMO SnO2) exhibit specific energy densities that are the same as those of fossil fuels. The scientific literature of the prior art suggests that this is impossible. The same effect is observed even for non-AMO metal oxides (e.g., tin oxide, titanium dioxide, and / or iron oxide) when configured as electrodes and batteries according to the methods of the present disclosure. This suggests that the mechanism of operation of these materials as active materials is beyond what is currently known or taught.
[0191] As described herein, non-AMO metal oxides can be constructed as electrodes having an active material loading substantially lower than that taught in the prior art. For example, the active loading can be less than 50%, such as 30wt% to 40wt%, 20wt% to 25wt%, or in particular 21wt% or 33wt%. The electrode can be formed by repeatedly applying multiple layers of active material until the desired thickness is reached. Conductive carbon can also be stacked with the active material. Conductive carbon can be applied at the same or different loading density as the active material. For example, both the active material and the conductive carbon can be present at 20wt% to 25wt%, such as 21wt%. In some embodiments, it has been determined that applying the active material in multiple thin layers provides enhanced performance over a single thicker layer.
[0192] Reference now Fig.19 , shows a bar graph comparing the lithiation capacity of various metal oxides using standard construction techniques compared to construction techniques according to the present disclosure. High active material loading and other standard construction techniques were first used for AMO tin oxide, AMO iron oxide, and non-AMO tin oxide. The particle size of AMO tin oxide is on the order of 5 nm. The particle size of non-AMO tin oxide is on the order of 20 nm.
[0193] When used with standard construction techniques, AMO tin oxide produced a lithiation capacity of about 2000 mAh / g. When constructed as an electrode with a lower active material loading (e.g., about 21 wt%) in a layered arrangement with nanoparticle conductive carbon (also about 21 wt%), the lithiation capacity increased to over 10,000 mAh / g. When the same test was performed, the increase using AMO iron oxide was from slightly less than 2000 mAh / g to about 8000 mAh / g. Surprisingly, non-AMO tin oxide also increased from less than 2000 mAh / g to over 6000 mAh / g. The average increase using the high-capacity construction method was about 314%.
[0194] Battery performance is driven largely, if not almost entirely, by the chemical reactions that create a potential between the terminals. Most batteries or cells produce an "S" shaped discharge curve. Under a steady load or discharge rate, an initial slightly steep voltage drop is observed, followed by a slower voltage drop as the battery discharges. Towards the end of the battery's usable charge, a second, even steeper, dramatic voltage drop is observed. This phenomenon can be seen in the Fig. 20This is observed in the example discharge curves for alkaline (Zn / MnO2), Li-ion, lead-acid, NiCd, and NiMH batteries plotted in . Of course, this does not exhaust the list of battery chemistries that have S-shaped discharge curves, nor the list of chemistries with relatively high cut-off voltages. Known chemistries with cutoff voltages exceeding those observed according to the chemistry of the present disclosure include, but are not limited to: lead acid (1.75V), zinc carbon (0.75-9.0V), zinc-air (0.9V), mercuric zinc oxide (0.9V), alkaline (0.9V), rechargeable alkaline (0.9V), silver oxide (1.2V), nickel zinc (0.9V), nickel iron (0.75V), nickel-cadmium (0.9-1.05V), nickel hydride (1.0V), nickel metal hydride (0.9-1.05V), low self-discharge nickel metal hydride (0.9-1.05), lithium manganese dioxide (2.0V), lithium carbon monofluoride (2.0V), lithium iron disulfide (0.9V), lithium cobalt oxide (2.5V), lithium iron phosphate (2.0V), lithium manganese oxide (2.5V), lithium nickel cobalt aluminum oxide (3.0V) and lithium nickel manganese cobalt oxide (2.5V).
[0195] Most modern devices do not use or cannot take advantage of the final steep portion of the discharge curve, and once the voltage drops below the nominal voltage by any significant amount, the battery is considered "dead". The battery can then be recharged or discarded. Not only are modern devices not designed to be able to take advantage of the final discharge portion of a battery, but it may not be safe to attempt to do so in certain circumstances. For example, lithium-ion batteries are known to become unstable in certain circumstances as they continue to discharge as the voltage approaches zero.
[0196] On the other hand, battery chemistries and construction techniques such as those described herein produce a more linear discharge curve from fully charged (or less than fully charged) all the way down to zero volts (or at least as close to zero volts as is available with current devices). Fig.21 is a representative discharge curve for a battery cell constructed based on AMO tin according to the present disclosure.
[0197] Fig. 22 is a similar diagram of a non-AMO active material battery cell based on the construction method of the present invention.
[0198] from Figure 21-22It can be seen that the discharge curve is more or less straight compared to the curve for prior art types of batteries. If the discharge is started close to the capacity of the battery, there is some initial "steep" voltage drop. However, even if the discharge is all the way to zero, there is no sudden drop at the end of the cycle. In addition, a charge less than a full charge can be put back on the battery, and the behavior of the discharge curve can be predictable as shown. It should be understood that the rightmost portion of the curve for the battery of the prior art will be "wasted" because the battery cannot be safely discharged into this area of the curve. However, it has been observed here that there are no battery cell failures or unsafe operating conditions when the AMO and non-AMO type batteries of the present disclosure are deeply discharged. In addition, as can be seen from the graph (e.g., the nominal voltage is 1), the battery still has a lot of capacity available even when discharged below the nominal voltage.
[0199] Previously, even so-called deep discharged batteries have had their life shortened when they are continuously or repeatedly discharged deeply (e.g., to about 20% of rated capacity). The batteries and cells of the present disclosure are not only capable of being deeply discharged without adverse effects, but can also be ultra-deeply discharged. For the purposes of this disclosure, ultra-deep discharge refers to the discharge of a battery or single cell to less than 20% of rated capacity. In some embodiments, the discharge level drops to 20%, 15%, 10%, 5%, 1% or less of capacity. Moreover, ultra-deep discharge (e.g., to 0 detectable volts) does not unduly damage the capacity of the battery cell. In some embodiments, a full ultra-deep discharge may result in a capacity loss of approximately 0.2%. In various embodiments, a full ultra-deep discharge cycle results in a capacity loss of less than .3%, less than .25%, or less than .2%. In other words, the capacity loss caused by ultra-deep discharge is commensurate with the ordinary capacity loss seen with non-deep discharge or non-ultra-deep discharge (per unit power provided).
[0200] New methods of using specific battery types (those of the present disclosure) have been determined to be useful based on repeated deep discharges and ultra-deep discharges with little or no damage to the battery. In particular, new discharge and charge profiles are useful for batteries composed of acidified metal oxides according to the present disclosure. In addition to stopping the discharge of the battery at an arbitrary point (until the battery is within a sharp terminal decline range), the battery can also be used as long as it can operate with the load to which it is connected (and without causing battery failure or hazardous operating conditions).
[0201] In one embodiment, a battery constructed according to the present disclosure is used until the voltage drops to .01 V. The battery can then be fully charged (eg, 2.8 V) or partially charged and used again until the voltage drops to .01 V.
[0202] In another embodiment, a battery according to the present disclosure is used until the functional threshold of the silicon chip it is powering is reached, and then it is fully or partially charged and then used again.
[0203] Today, many chips and processors operate at voltages of 1.0V or less. Devices designed to reduce consumption can operate at even lower voltages. Therefore, traditional lithium-ion batteries, which have a safety functional minimum voltage of approximately 2.8 to 3V, still provide a higher voltage than is required to operate many chips. Although this potential cannot be safely utilized due to the instability of further deep discharge of lithium-ion batteries. On the other hand, with a battery constructed in accordance with the present disclosure, virtually all available power can be safely obtained. Since the battery cells and batteries constructed in accordance with the present disclosure can be discharged to .01V or less, the only practical lower limit is the load or device being powered. As newer devices with even lower operating voltages are developed, batteries constructed in accordance with the present disclosure and used in accordance with the methods described herein can provide both longer times between charges and more efficient use of energy.
[0204] In prior art devices utilizing conventional 3.6V Li-Ion technology, an inefficient step-down transformer or voltage divider may be required to provide the correct operating voltage to a logic board or newer chip that requires a substantially lower operating voltage than the battery supplies. Batteries constructed in accordance with the present disclosure can provide a maximum open circuit voltage (OCV) of 2.8 or less and a nominal voltage of approximately 1.0. Thus, a large amount of the power available from a battery cell in accordance with the present disclosure can be used by the logic or chip without the need for any step-down device. In some cases, this can simplify device design and improve efficiency in almost every possible scenario.
[0205] Since batteries and cells constructed in accordance with the present disclosure can easily supply more than enough voltage for many silicon chips, step-down devices may be required at the initial high end of the discharge curve. However, these devices can be ignored in the later part of the curve when they are not needed. This has the added effect of increasing efficiency as the battery or cell discharges. Thus, the "latter half" of the discharge may actually provide more usable energy or longer operating time than the "first half".
[0206] Conventional lithium-ion batteries require a charging voltage of 3.8V, and ideally 4.2V. Such voltages may be difficult to provide to solar cells (a single cell may only provide about .5V) or other low voltage power sources. However, it should be understood that the battery according to the present disclosure does not have to have such a voltage to charge, and any stable voltage applied to the cell or battery above the current discharge voltage will result in at least some recharging. Therefore, even a low voltage or weak voltage power source, such as a single solar cell, may be able to provide a usable charge to the battery or cell. Because the battery constructed according to the present disclosure is not harmed by low voltage charging and discharging, in some cases, the battery can be cycled to the material limit only at low voltage.
[0207] In other embodiments, the battery or battery cell may sometimes be operated at a low voltage charge or discharge cycle (e.g., just below the nominal voltage of the battery cell) and then operated at a higher voltage (e.g., up to a full open circuit voltage such as 2.8 V or 3.2 V). Batteries according to the present disclosure may be operated at a higher voltage to power devices that require such relatively high voltages (e.g., greater than 1 V) and then used to power low voltage devices when the discharge voltage drops below a predetermined distance below the nominal value.
[0208] It should be understood that the various charging and discharging options for batteries or battery cells according to the present disclosure can occur at a variety of charging and discharging rates. Naturally, the faster the discharge rate, the faster the battery will be exhausted, but the battery or battery cell may still be discharged substantially to zero. In some cases, a first discharge rate may be used for a first portion of the discharge, and a second discharge rate may be used for a second portion of the discharge. Multiple discharge rates may be used at different times, or depending on the needs of the battery-powered device. Similarly, for charging rates, faster or slower charging rates may be used at any time during the discharge curve (as long as sufficient voltage is available), depending on the charging resources available at the time.
[0209] Batteries and battery cells according to the present disclosure may also be used so that the battery or battery cell is never charged above its nominal voltage, or is never charged above another predetermined threshold. Likewise, the lower voltage threshold may be based on an absolute minimum lower voltage useful for an attached load, or based on another need of the user, for discharge. These thresholds may also be dynamically re-determined or changed based on the resources attached to the battery or battery cell and / or the current use or load.
[0210] In various embodiments of methods of using a battery or battery cell according to aspects of the present disclosure, the battery cell may be discharged to 99%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 1%, 0.1%, or other values prior to charging. Charging may occur to restore the battery to 100%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 1%, .1%, or other portions of capacity prior to charging again. At this point, the discharge may return the battery to any state of discharge prior to the charged state. Similarly, the discharge and charge rates may vary widely. For example, the discharge rate can be from .01C or lower to 1C or higher. The charge rate can also be, for example, from .01C or lower to 1C or higher.
[0211] All references throughout this application, such as patent documents including issued or granted patents or their equivalents, patent application publications, and non-patent literature documents or other source materials, are hereby incorporated by reference in their entirety as if individually incorporated by reference.
[0212] All patents and publications mentioned in the specification are indicative of the technical level of those skilled in the art to which the invention belongs. The references cited herein are incorporated herein by reference in their entirety to indicate the state of the art as of their filing date in some cases, and it is intended that this information may be used herein, if necessary, to exclude (e.g., deny) specific embodiments in the prior art. For example, when claiming a compound, it should be understood that compounds known in the prior art, including certain compounds disclosed in the references disclosed herein (particularly referenced patent documents), are not intended to be included in the claims.
[0213] When a group of substituents is disclosed herein, it is understood that all individual members of those groups and all subgroups and classes that can be formed using substituents are disclosed separately. When Markush groups or other groups are used herein, all individual members of the groups and all possible combinations and subcombinations of the groups are individually included in the present invention. As used herein, "and / or" means that one, all or any combination of the items separated by "and / or" in the list is included in the list; for example, "1, 2 and / or 3" is equivalent to "1" or "2" or "3" or "1 and 2" or "1 and 3" or "2 and 3" or "1, 2 and 3".
[0214] Unless otherwise stated, each formula or component combination described or illustrated can be used for implementing the present invention.The specific name of the material is intended to be exemplary, because it is known that those of ordinary skill in the art can name the same material differently.It will be appreciated by those of ordinary skill in the art that methods, device elements, starting materials and synthetic methods other than those specifically illustrated can be adopted in the practice of the present invention without excessive experiments.All functional equivalents known in the art of any such method, device element, raw material and synthetic method are included in the present invention.Whenever a range (e.g., temperature range, time range or composition range) is given in the specification, all intermediate ranges and sub-ranges and all individual values included in the range given are intended to be included in the present disclosure.
[0215] As used herein, "comprising" is synonymous with "including," "containing," or "characterized by," and is inclusive or open-ended and does not exclude additional, unlisted elements or method steps. As used herein, "consisting of" excludes any element, step, or ingredient not specified in the claim elements. As used herein, "consisting essentially of" does not exclude materials or steps that do not substantially affect the basic and novel characteristics of the claim. Any recitation of the term "comprising" herein, particularly in the description of the components of the composition or in the description of the elements of the device, should be understood to include those compositions and methods consisting essentially of and consisting of the components or elements recited. The invention described herein may be suitably practiced in the absence of any element or limitation not specifically disclosed herein.
[0216] The terms and expressions that have been adopted are used as terms of description rather than terms of limitation, and the use of such terms and expressions is not intended to exclude any equivalents of the features shown and described or parts thereof, but it should be recognized that various modifications are possible within the scope of the invention claimed. Therefore, it should be understood that although the present invention has been specifically disclosed through preferred embodiments and optional features, those skilled in the art may reclassify modifications and variations of the concepts disclosed herein, and such modifications and variations are considered to be within the scope of the invention as defined by the claims.
Claims
1. A method for deep discharge of a battery cell, the battery cell comprising two electrodes and an electrolyte located between the two electrodes, at least one of the two electrodes comprising an acidified metal oxide nanomaterial having a size less than 1 micron, the method comprising: performing a plurality of charge cycles and discharge cycles on the battery cell, wherein the discharge level of each discharge cycle is less than 20% of the full capacity of the battery cell; wherein each discharge cycle results in a loss of less than 0.3% of the total available capacity of the battery cell, wherein the acidified metal oxide nanomaterial comprises acidified iron oxide, acidified tin oxide, acidified antimony oxide, acidified bismuth oxide, acidified titanium oxide, acidified zirconium oxide, acidified manganese oxide or acidified indium oxide; wherein the battery voltage of at least one discharge cycle drops to 0.01V; The acidified metal oxide nanomaterial accounts for 1 to 33 wt % of the cathode.
2. The method according to claim 1, wherein: Each discharge level of each discharge cycle reaches a detectable zero volt battery voltage.
3. The method according to claim 1, wherein: Each discharge cycle includes a first portion, wherein the battery cell is electrically connected to a first load requiring a first voltage, and a second portion, wherein the battery cell is electrically connected to a second load requiring a second voltage, and wherein the first voltage is higher than the second voltage.
4. The method according to claim 1, wherein: Each charging cycle is performed at a voltage less than the maximum voltage open circuit voltage of the battery cell.
5. The method according to claim 1, wherein: Each charging cycle is performed at a voltage greater than the maximum open circuit voltage of the battery cell.
6. The method according to claim 1, wherein: Each charging cycle is performed at a voltage level that is higher than the current voltage of the battery cell but lower than the maximum open circuit voltage of the battery cell.
7. The method according to claim 1, wherein: Each charging cycle is performed at a voltage level that is higher than the current voltage of the battery cell but lower than the nominal voltage of the battery cell.
8. The method according to claim 1, wherein: Each charging cycle provides less than a full charge of the battery cell.
9. A method of using a battery having at least one battery cell having a cathode having an active material loading of less than 80%, the method comprising performing a plurality of charge cycles and discharge cycles on the battery, wherein: The discharge level of each discharge cycle is less than 20% of the full capacity of the battery, wherein at least a portion of at least one discharge cycle occurs at a discharge voltage of less than 0.7 volts, and wherein each discharge cycle results in a loss of less than 0.3% of the total available capacity of the battery; Wherein, the acidified metal oxide nanomaterial includes acidified iron oxide, acidified tin oxide, acidified antimony oxide, acidified bismuth oxide, acidified titanium oxide, acidified zirconium oxide, acidified manganese oxide or acidified indium oxide, and wherein the acidified metal oxide nanomaterial accounts for 1 to 33wt% of the cathode; at least a portion of at least one discharge cycle is to achieve a battery voltage of 0.01V.
10. The method according to claim 9, wherein: At least one discharge cycle is down to a lowest usable voltage for a load attached to the battery.
11. The method according to claim 9, wherein: The discharge level for at least one of the discharge cycles is a detectable zero volt battery voltage.
12. The method according to claim 9, wherein: At least one of the discharge cycles includes a first portion in which the battery is electrically connected to a first load requiring a first voltage and a second portion in which the battery cell is electrically connected to a second load requiring a second voltage and wherein the first voltage is higher than the second voltage.
13. The method according to claim 9, wherein: At least one charging cycle is performed at a voltage less than the maximum voltage open circuit voltage of the battery.
14. The method according to claim 9, wherein: At least one charging cycle is performed at a voltage greater than the maximum open circuit voltage of the battery.
15. The method according to claim 9, wherein: At least one charging cycle is performed at a voltage level that is higher than the current voltage of the battery but less than the maximum open circuit voltage of the battery.
16. The method according to claim 9, wherein: Each charging cycle is performed at a voltage level that is higher than the battery's current voltage but less than the nominal voltage of the battery cell.
17. The method according to claim 9, wherein: Each charging cycle provides less than a full charge of the battery.
18. A method of using a battery having at least one battery cell in a cathode having an active material loading of less than 80%, the method comprising performing a plurality of charge cycles and discharge cycles on the battery, wherein: The discharge level of each discharge cycle reaches a depth of at least 80% of the capacity, the minimum battery voltage is 0.01V, and each discharge cycle causes a loss of less than 0.3% of the total available capacity of the battery cell, wherein the active material of the cathode includes an acidified metal oxide nanomaterial selected from the group consisting of acidified iron oxide, acidified tin oxide, acidified antimony oxide, acidified bismuth oxide, acidified titanium oxide, acidified zirconium oxide, acidified manganese oxide or acidified indium oxide; wherein the acidified metal oxide nanomaterial accounts for 1 to 33wt% of the cathode.
19. The method of claim 18, wherein the discharge level of at least one discharge cycle reaches a detectable zero volt battery voltage.
Citation Information
Patent Citations
Hexacyanometallates as highly conducting solid electrolytes for batteries
US20170069931A1
Battery performance monitor
US20090027056A1
Lithium secondary cell with high charge and discharge rate capability and low impedance growth
US20140242445A1